Deciphering Idioms: A Deep Dive into Elemental Force of Nature Movie Script - Puspitasari, Desi; Dwi Yuliawati, Denies; Hanayanti, Citra Siwi (Institut Agama Islam Negeri Parepare, 2024)
Idioms, intricate combinations of words whose meaning eludes straightforward interpretation, play an essential role in native speakers' discourse. It imbues speeches with a sense of fluency and creativity. Mastering idiomatic expressions is imperative for learners seeking linguistic authenticity and lexical proficiency. Thus, it is an urge to be mastered by the learners, especially English for Foreign Language (EFL) learners. This study aimed to explore the types of idioms in the Elemental Force of Nature Movie Script, employing O'Dell and McCarthy's framework. It utilized a qualitative study using content analysis. The researchers used documentation as the primary data collection method. as the data was taken from the Elemental: Force of Nature movie script dialogues. The findings unveil forty-one idioms in Elemental: Force of Nature movie. This research found four similes, two proverbs, four clichés, and thirty-three fixed statements. However, the most dominant type found in this movie was the fixed statement. It is expected that this research can provide additional insight into the types of idiomatic expressions. In addition, this study also provided valuable implications for the English learners, especially who study literary works.